Marion et Nicolette : intersectionnalité et autonomisation - María Pilar Suárez (Perspectives Médiévales)
In this paper, we propose an approach to two female literary figures: Nicolette, the eponymous character of the chantefable, and Marion, the shepherdess of the Jeu de Robin et Marion. Both share the common ground of being excluded from the courtly universe and from the status of "superiority" that it grants to women over men. They are indeed characterized by their "intersectionality," which nevertheless makes them capable of far exceeding the presuppositions emanating from a predominantly male "official" world. We study the modulations of these characters based on the notion of point of view (Alain Rabatel), enriched by that of "situated knowledges" developed by Donna Haraway. The implementation of these concepts allows us to analyze the discursive dynamics through which the respective paths of the two women are drawn, leading in both cases to their empowerment-autonomization.